The Comparison of Treffinger Model to Rewrite an Anecdote and Short Story Folklore Text for Class X of SMA Negeri 6 Padang - Hayu Afdetis Mana, Lira; Rahmi, Afrini; Harti, Laspida; Harnon; Rahmat, Wahyudi (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2023)
The purpose of this study was to describe the comparison of using Treffinger model to rewrite anecdotal and short story folklore texts for class X students of SMA Negeri 6 Padang. The type of the research is quantitative research with experimental method. The population of this research are 255 students of class X of SMA Negeri 6 Padang 2022/2023 academic year. Sample of the research was taken by using simple random sampling technique. The instrument of the research was writing test of anecdotal and short story folklore text. After treating the sample classes by using Treffinger model, X IPA 2 and X IPS 4 was tested to write anecdotal text, X IPA 1 and X IPS 3 was treated to write short story folklore text. The results of the research were as follows; first, students’ average score in writing short story folklore text who taught by using the Treffinger model were of 82.67 with good category (range of 76% -85%). Second, students' average score in writing anecdotal text by using Treffinger model were 75.50 with more than adequate category (range of 66%-75%). Third, there is a significant comparison between students’ ability to rewrite anecdotal texts and short story folklore text by using Treffinger model at class X students of SMA Negeri 6 Padang.